Achieving the best results at the Games of the Olympiad by elite judoka - Timofeev, V. D.; Makarov, V. V.; Brainin, A. A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to conduct a comparative analysis of the achievement of the best results by judo athletes of the leading national teams at the Olympiad Games and the main competitions in the training cycle that preceded these Games, as well as to identify the information content of other indicators of the realization of the potential of national judo teams.